2018
DOI: 10.1016/j.molmet.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Constant hepatic ATP concentrations during prolonged fasting and absence of effects of Cerbomed Nemos® on parasympathetic tone and hepatic energy metabolism

Abstract: ObjectiveBrain insulin-induced improvement in glucose homeostasis has been proposed to be mediated by the parasympathetic nervous system. Non-invasive transcutaneous auricular vagus nerve stimulation (taVNS) activating afferent branches of the vagus nerve may prevent hyperglycemia in diabetes models. We examined the effects of 14-min taVNS vs sham stimulation by Cerbomed Nemos® on glucose metabolism, lipids, and hepatic energy homeostasis in fasted healthy humans (n = 10, age 51 ± 6 yrs, BMI 25.5 ± 2.7 kg/m2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…the rhythmic contractions of the stomach 13 . In contrast, 14 min of taVNS did not modulate the autonomic tone to visceral organs up to 120 min post stimulation in a recent study 17 .…”
mentioning
confidence: 72%
“…the rhythmic contractions of the stomach 13 . In contrast, 14 min of taVNS did not modulate the autonomic tone to visceral organs up to 120 min post stimulation in a recent study 17 .…”
mentioning
confidence: 72%
“…RMSSD, pNNx, RSA, or HF HRV; Laborde et al, 2017; Task Force of The European Society of Cardiology & The North American Society of Pacing and Electrophysiology, 1996). Other indices, including the LF/HF ratio which was found to be influenced by tragus stimulation in some studies (Antonino et al, 2017;Clancy et al, 2014;Weise et al, 2015) but not in others (Couck et al, 2017;Gancheva et al, 2018), are influenced by other factors than vagal activity, and thus should not be interpreted as a definite sign that the vagus nerve is activated.…”
Section: Recommendations and Challenges For Future Researchmentioning
confidence: 87%
“…In a second study, the authors found that one hour of right ear cymba concha stimulation did not affect any HRV parameter after controlling for confounders (De Couck et al, 2017). Similarly, in 10 healthy individuals, stimulation of the left cymba concha did not significantly affect HF HRV (Gancheva et al, 2018). During a fear conditioning procedure, stimulation of the left cymba concha did not significantly affect RMSSD throughout generalization and extinction learning (A.…”
Section: Markers Of Vagal Activity 21 Heart Rate Variabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…Other more physiologically oriented studies have investigated the influence of tVNS on cardiac activity (Brock et al, 2017 ; De Couck et al, 2017 ; Lamb et al, 2017 ; Gancheva et al, 2018 ; Borges et al, 2019 ; Bretherton et al, 2019 ; Koenig et al, 2019 ; Paleczny et al, 2019 ; Tobaldini et al, 2019 ; Tran et al, 2019 ); autonomic outflow (Sclocco et al, 2017 ); sympathetic nerve activity (Clancy et al, 2014 ) or cardiac baroreflex sensitivity (Antonino et al, 2017 ); atrial fibrillation (Stavrakis et al, 2015 ); cardiac mechanical function (Tran et al, 2019 ); vagal sensory evoked potentials (Fallgatter et al, 2003 , 2005 ; Polak et al, 2009 ; Leutzow et al, 2013 ); persistent hiccups (Schulz-Stübner and Kehl, 2011 ); visual bistable perception (Keute et al, 2019a ); nociceptive neuromodulation (Napadow et al, 2012 ; Busch et al, 2013 ; Laqua et al, 2014 ; Usichenko et al, 2017b ; Janner et al, 2018 ); tumor necrosis factor-alpha (Brock et al, 2017 ); hepatic energy metabolism (Gancheva et al, 2018 ); whole blood culture-derived cytokines and chemokines (Lerman et al, 2016 ); salivary hormones (Ventura-Bort et al, 2018 ; Koenig et al, 2019 ; Warren et al, 2019 ); pupil diameter (Warren et al, 2019 ); gastroduodenal or gastrointestinal motility (Frøkjaer et al, 2016 ; Juel et al, 2017 ); muscle activity in the gastrointestinal tract (Hong et al, 2019 ), gastric frequency (Teckentrup et al, 2020 ); electroencephalography (Hyvärinen et al, 2015 ; Keute et al, 2018 ; Lewine et al, 2019 ) and event-related potentials (Lewine et al, 2019 ), specifically the P3/P300 event-related potential (Ventura-Bort et al, 2018 ; Warren et al, 2019 ); cortical excitability (Capone et al, 2015 ) and changes in blood-oxygen-level-dependent (BOLD) functional Magnetic Resonance Imaging (fMRI) (Kraus et al,...…”
Section: Modes Of Applicationmentioning
confidence: 99%